2018
DOI: 10.1002/acm2.12410
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of intrafractional tumor motion estimation based on 4D‐CBCT using diaphragm as surrogate

Abstract: PurposeTo investigate the intrafractional stability of the motion relationship between the diaphragm and tumor, as well as the feasibility of using diaphragm motion to estimate lung tumor motion.MethodsEighty‐five paired (pre and posttreatment) daily 4D‐CBCT images were obtained from 20 lung cancer patients who underwent SBRT. Bony registration was performed between the pre‐ and post‐CBCT images to exclude patient body movement. The end‐exhalation phase image of the pre‐CBCT image was selected as the reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…We compared the motion between the diaphragm and the tumor by breathing phase matching and found that the maximum directional mean deviation was −1.8 mm. These results were similar to those of Zhou et al [ 24 ], indicating that the use of the diaphragm as a tracking surrogate in the CyberKnife tracking module provides similar performance to that of the movement of the tumor itself in the SI direction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We compared the motion between the diaphragm and the tumor by breathing phase matching and found that the maximum directional mean deviation was −1.8 mm. These results were similar to those of Zhou et al [ 24 ], indicating that the use of the diaphragm as a tracking surrogate in the CyberKnife tracking module provides similar performance to that of the movement of the tumor itself in the SI direction.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown a good correlation between the diaphragm and liver tumors in SI and AP directions and indicated that the movement amplitude in the mediolateral direction was small and likely clinically irrelevant [ 16 , 17 ]. Based on the linear model, Cerviño et al [ 23 ] and Zhou et al [ 24 ] reported that the per-phase position, mean position, and excursion estimation errors were 1.12±0.99 mm, 0.97±0.88 mm, and 0.79±0.67 mm, respectively. Intrafractional per-phase tumor position estimation error, mean position error, and excursion error were within 3 mm, 95%, 96%, and 99% of the time, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, image processing techniques to detect tumor itself in kilovoltage [ 20 , 21 ] or megavoltage [ 22 , 23 ] images without the fiducial markers have been reported. It has also been reported that an anatomical feature such as the diaphragm could be used instead of the metal markers [ 24 , 25 ]. These kinds of techniques are considered to be useful for patients who cannot have markers inserted.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopic imaging in the linear accelerator is a conventional tool for position verification before radiotherapy. Some studies have reported using fluoroscopic imaging for direct tumor tracking with template matching applied as the localization algorithm (7)(8)(9)(10). However, the problem with tracking tumor motion in fluoroscopic images is that it is difficult to identify tumor targets because of the poor image contrast.…”
Section: Introductionmentioning
confidence: 99%